Comparative study of flavor precursors, volatile compounds and sensory between Malaysian and Ghanaian cocoa beans - Rahmat Mohamed; Aminah Abdullah; Ken, Choy Yap; Wan Aida Wan Mustapha (Penerbit Universiti Kebangsaan Malaysia, 2019)
The aim of this work was to compare quantitatively the flavor precursor constituents between unroasted Ghanaian and Malaysian cocoa beans. Furthermore, the effect of roasting on the flavor development was also characterized based on the volatile compounds and sensory analysis. Sensory analysis results showed a significant difference (p<0.05) for the cocoa attribute, sour and overall acceptability between samples. Ghanaian cocoa beans showed higher scores for cocoa and overall acceptability attributes, while Malaysian samples showed a higher acidic attribute. Meanwhile, other attributes such as fruity, bitterness, astringent, raw and viscosity do not show a significant difference (p>0.05) between samples. Effects of flavor pre-cursors such as organic acids (citric acid, lactic acid, acetic acid), sugars (glucose, sucrose, fructose), free amino acids (asidic, bases, hydrophobic, polyphenols), and volatile compounds (alcohol, ketones, aldehydes, esters, pyrazine, acetic acid) are presented. Ghanaian cocoa beans were found to be much more acceptable in term of taste and flavors. Importantly, the amount of organic acids found in the beans could be a potential marker, contributed to the overall acceptability level for cocoa beans.